TTL prediction schemes and the effects of inter-update time distribution on wireless data access - Fang, YG; Haas, ZJ; Liang, B; Lin, YB (My University, 2004)
Modern mobile networks, such as GPRS and UMTS, support wireless data applications. One successful example is the ever popular i-Mode in Japan. Wireless data services ( wireless Internet) become more important as more and more customers of handheld devices enjoy the convenience of the ubiquitous computing. To improve the effective wireless data access, the time-to-live (TTL) management for data entries becomes important due to its use in effective caching design. In this paper, we study three TTL prediction schemes and investigate the effects of the inter-update time distribution on the wireless data access. Performance analysis is carried out via simulations as well as analytical modeling. We expect our results will be useful for the future wireless data access systems, in which transmission power for mobile devices is more limited.
Keywords: time-to-live (TTL); weakly consistency; wireless data; caching